NGIWY-Amide: A Bioinspired Ultrashort Self-Assembled Peptide Gelator for Local Drug Delivery Applications - Nikoleta F. Theodoroula; Christina Karavasili; Manos C. Vlasiou; Alexandra Primikyri; Christia Nicolaou; Alexandra V. Chatzikonstantinou; Aikaterini-Theodora Chatzitaki; Christos Petrou; Nikolaos Bouropoulos; Constantinos K. Zacharis; Eleftheria Galatou; Yiannis Sarigiannis; et al. (Pharmaceutics, 2022)
Fibrillar structures derived from plant or animal origin have long been a source of inspiration for the design of new biomaterials. The Asn-Gly-Ile-Trp-Tyr-NH2 (NGIWY-amide) pentapeptide, isolated from the sea cucumber Apostichopus japonicus, which spontaneously self-assembles in water to form hydrogel, pertains to this category. In this study, we evaluated this ultra-short cosmetic bioinspired peptide as vector for local drug delivery applications. Combining nuclear magnetic resonance, circular dichroism, infrared spectroscopy, X-ray diffraction, and rheological studies, the synthesized pentapeptide formed a stiff hydrogel with a high β-sheet content. Molecular dynamic simulations aligned well with scanning electron and atomic-force microscopy studies, revealing a highly filamentous structure with the fibers adopting a helical-twisted morphology. Model dye localization within the supramolecular hydrogel provided insights on the preferential distribution of hydrophobic and hydrophilic compounds in the hydrogel network. That was further depicted in the diffusion kinetics of drugs differing in their aqueous solubility and molecular weight, namely, doxorubicin hydrochloride, curcumin, and octreotide acetate, highlighting its versatility as a delivery vector of both hydrophobic and hydrophilic compounds of different molecular weight. Along with the observed cytocompatibility of the hydrogel, the NGIWY-amide pentapeptide may offer new approaches for cell growth, drug delivery, and 3D bioprinting tissue-engineering applications.